PREDIKSI TAHANAN DAN PROPULSI WAHANA ANGKUT ANJUNGAN LEPAS PANTAI PASKA OPERASI (ALPO) - Kusnindar Priohutomo (Jurnal Teknologi Maritim, 2019)
Indonesia as an International Maritime Organizaion (IMO) member country has an obligation to clean shipping line from offshore structure that are no longer in use. The cost of decommisioning offshore structure has very high costs, especially for rent ship which is used to move offshore structures from sea to land. For that the Indonesian Government has a plan to have its own decommissioning vessel. Because the cost of ship building is not cheap, the aspect of engine selection is an important factor in the design stage. In this paper, analysis for ship resistance is predicted using Rhinoceros dan Orca 3D. Method for analysis ship resistenace is Holtrop Method. From the results of software analysis obtained results for resistance of bare hull at a speed of 14 knots at 78.57 kN and for total resistance at a speed of 14 knots at 90.35 kN. For effective horse power (EHP) at 14 knots at 872.67 HP and for brake horse power (BHPmcr) at 14 knots at 1866.68 HP.